Approaches of gender and intercultural perspectives in health - Vincx, Laura (2019)
In Peru there are great gender and intercultural gaps, particularly in the health sector. These gaps lead to discrimination, maternal and infant deaths, and mistreatment and dehumanization of medical attention. To improve the quality of healthcare, the SISTEC Program used workshops in gender and interculturality as its methodology, organizing 44 in 5 regions and training 837 healthcare professionals. Capitalizing this experience, a variety of factors to improve the results of these workshops stood out, such as the selection of participants, cultural adaptation and the methodology used. The workshops led to socio-cultural changes in both work and personal spheres, but their sustainability depends strongly on the institutionalization strategies used. In conclusion, trainings can be a useful methodology to drive sustainable appropriation of gender and intercultural perspectives, provided that they are part of a more holistic and adequately planned strategy where workshops serve as the starting point to promote change.